MOHO DEPTH VARIATION BENEATH SOUTHWESTERN JAPAN REVEALED FROM THE VELOCITY STRUCTURE BASED ON RECEIVER FUNCTION INVERSION - Shiomi K.; Obara K.; Sato H. (My University, 2006)
The Philippine Sea plate is subducting under the Eurasian plate beneath the Chugoku-Shikoku region, southwestern Japan. We have constructed depth contours for the continental and oceanic Mohos derived from the velocity structure based on receiver function inversion. Receiver functions were calculated using teleseismic waveforms recorded by the high-density seismograph network in southwestern Japan. In order to determine crustal velocity structure, we first improved the linearized time-domain receiver function inversion method. The continental Moho is relatively shallow (~ 30 km) at the coastline of the Sea of Japan and at the Seto Inland Sea, and becomes deeper-greater than 40 km-around 35°N and 133.8°E. Near the Seto Inland Sea, a low-velocity layer of thickness 10 km lies under the continental Moho. This low-velocity layer corresponds to the subducting oceanic crust of the Philippine Sea plate. The oceanic Moho continues to descend from south to northwest and exhibits complicated ridge and valley features. The oceanic Moho runs around 25 km beneath the Pacific coast and 45 km beneath the Seto Inland Sea, and it extends to at least to 34.5°N. The depth variation of the Moho discontinuities is in good qualitative agreement with the concept of isostasy. From the configurations of both the continental and oceanic Mohos, we demonstrate that the continental lower crust and the subducting oceanic crust overlap beneath the southern and central part of Shikoku and that a mantle wedge may exist beneath the western and eastern part of Shikoku. The southern edge of the overlapping region coincides with the downdip limit of the slip area of a megathrust earthquake. © 2006 Elsevier B.V. All rights reserved.
Keywords: CONTINENTAL MOHO; OCEANIC MOHO; PHILIPPINE SEA PLATE; RECEIVER FUNCTION; SOUTHWESTERN JAPAN